Pemberian Topikal Asi Terhadap Pelepasan Tali Pusat Bayi Baru Lahir di PMB Wilayah Kerja Puskesmas Kasarangan - Nabella Faizah, Muthia; Elvine Ivana Kabuhung; Frani Mariana (Institut Nalanda, 2024)
Umbilical cord care is the act of treating and tying the umbilical cord of a newborn baby, to avoid infection. One method of umbilical cord care uses breast milk. Topical breast milk treatment is very efficient because it does not require costs, is easy to apply and is a non-invasive technique, so it is safe to do. This study aims to determine the effect of topical breastfeeding on the release of the umbilical cord of newborn babies in the PMB working area of the Kasarangan Community Health Center. This research used quasi experimental with a posttest only with control group approach. The total sample was 20 respondents divided into 2 groups, namely 10 respondents in the intervention group and 10 respondents in the control group used consecutive sampling technique. The research instruments were respondent characteristics and observation sheets. Data analysis used the Mann Whitney test with a confidence level of 95%. The duration of umbilical cord removal for newborns in the intervention group in the fast category was 7 babies (70%) and in the control group in the normal category was 8 babies (80%). There was an effect of topical breastfeeding on the release of the umbilical cord of newborn babies in the PMB working area of the Kasarangan Community Health Center (p=0,028 <0,05). Routine topical administration of breast milk (2x a day) can speed up the release of a newborn's umbilical cord compared to non-routine (<2x a day).